Hubungan kemandirian belajar dengan hasil belajar peserta didik - Syahfa, Ardhea Nur; Marmoah, Sri; Adi, Fadhil Purnama (Jurnal Pendidikan Dasar, 2023)
This study aims to analyze how big the relationship between the Pancasila Student Profile and student learning outcomes at SD Ta'mirul Islam Surakarta. This research is a correlational quantitative research. The data source for this research was students of class II and III of SD Ta'mirul Islam Surakarta. The sampling technique was carried out by means of random sampling. Data collection was carried out using questionnaires and cognitive test questions. Validity test using content validity test and reliability test with SPSS 24.0. Data analysis consisted of analysis prerequisite tests and hypothesis testing. The analysis prerequisite test consists of a normality test and a linearity test, while the hypothesis test uses a product moment correlation test, and multiple correlation tests. The results of this study are as follows: The results of the independent learning questionnaire amounted to 27 trials carried out by 32 respondents, the validity results obtained were 2 invalid residual questions. In the class 2 cognitive test instrument, there were 15 questions, then a trial was carried out by 32 respondents, the validity results were 10 questions, 5 residual questions were invalid. In the class 3 cognitive test instrument, there were 15 questions, then a trial was carried out by 32 respondents, the validity results obtained were 3 residual questions that were not valid. The results of the study with the product correlation test obtained a significance value of 0.000 <0.05 that the X1 variable, namely learning independence, had a convincing influence on the Y variable, namely student learning outcomes. results. Based on the data above, there is also an interpretation of the product moment correlation of 0.725 which is included in the category of strong relationship level.